2009
DOI: 10.1038/sc.2009.156
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to continuous intrathecal baclofen infusion can be reversed by pulsatile bolus infusion

Abstract: Study design: Pilot study. Objective: To study the effect of pulsatile bolus infusion of intrathecal baclofen (ITB) on daily ITB dose, in patients showing dose increases, probably due to tolerance. Setting: Department of neurology and neurosurgery, University Medical Center Groningen, the Netherlands. Methods: Data on dosages and clinical efficacy were gathered from four patients who were switched from continuous to pulsatile bolus infusion of ITB, because of the probable diagnosis of tolerance to ITB. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 21 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…). Assuming the previously described steps have been undertaken without detection of system abnormalities, interventions for tolerance include decreasing the concentration of baclofen solution with a concomitant increase in flow rate, utilization of periodic bolus/flexible dosing, serial decrements in dosing followed by a retitration, or a drug holiday .…”
Section: System Malfunction Investigationmentioning
confidence: 99%
“…). Assuming the previously described steps have been undertaken without detection of system abnormalities, interventions for tolerance include decreasing the concentration of baclofen solution with a concomitant increase in flow rate, utilization of periodic bolus/flexible dosing, serial decrements in dosing followed by a retitration, or a drug holiday .…”
Section: System Malfunction Investigationmentioning
confidence: 99%
“…The versatility of TDD hardware and software has evolved from devices capable of simple continuous nonprogrammable flow, to TDD systems with time and daily‐programmable variable modes . Optimizing programming algorithms received attention after physicians treating spasticity demonstrated that baclofen tolerance can be reversed when the agent is administered by daily timed bolus rather than continuous infusion . TDD patients may now use a wireless device to administer physician‐prescribed boluses of intrathecal analgesics to treat incident pain or unpredictable fluctuations in daily pain .…”
Section: Introductionmentioning
confidence: 99%
“…Different treatment options can be considered such as a drug holiday (i.e. a period without intrathecal baclofen) or a change in the drug administration to complex continuous or to pulsative administration instead of simple continuous [27,30]. Draulans [7], on the other hand, believes that long-term dosage stabilization of ITB may indicate that tolerance does not exist and that the need for dose increase may instead represent an unrecognized catheter malfunction.…”
Section: Discussionmentioning
confidence: 97%